The Influence of Service Quality, Product Variety, and Location on Customer Satisfaction at Bapade's Coffee Kemanggisan West Jakarta - Pratama, Andhika Yoga; Hardini, Resti; Digdowiseiso , Kumba (CV ODIS, 2023)
This study aims to determine the influence between Service Quality, Product Variety, and Location on Customer Satisfaction at Bapades Coffee Kemanggisan West Jakarta. The sample studied in this study amounted to 121 respondents, data collection methods using questionnaire methods with Likert scales and data analysis techniques using Multiple Linear Analysis using the SPSS program version 23. The results of the study have a regression equation Y = 0.616 X1 + 0.53 X2 + 0.192 X3 Based on the results of the T Test shows an influence between Service Quality (X1) on Customer Satisfaction (Y) based on T count 6,949 > T table 1,660 and sig value 0.000 < 0.50. For the variable Product Variation (X2) does not have a significant effect on Customer Satisfaction (Y) based on T, calculate 0.738 < 1,660 T table and sig value 0.462 > 0.50. For the Location variable (X3) shows an influence on Customer Satisfaction (Y) based on the calculated T value of 2,183 > 1,660 T table and the sig value of 0.31 < 0.50. The results of this study have concluded that the variables of Service Quality and Location have a significant effect on Customer Satisfaction. Another conclusion from this study is that Product Variation does not have a significant effect on Customer Satisfaction.